Criminal Sanctions for Perpetrators of Corruption under Law No. 1 of 2023 on the Criminal Code (KUHP) in Indonesia - Junaidin Junaidin; Syamsuddin Syamsuddin; Nurul Izzati Mardiah (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
Corruption in Indonesia is classified as an extraordinary crime due to its systemic destructive impact. The enactment of Law No. 1 of 2023 on the Criminal Code (National Criminal Code) has brought about fundamental changes that raise the potential for regulatory overlap with Law No. 31 of 1999 in conjunction with Law No. 20 of 2001 on the Eradication of Corruption Crimes (Anti-Corruption Law). The introduction of this new codification has raised public concerns regarding a potential weakening of the deterrent effect due to a reduction in the minimum mandatory prison sentences. This study aims to conduct an in-depth analysis of criminal sanction policies for perpetrators of corruption offenses from the perspective of the National Criminal Code and to examine their relationship with the Anti-Corruption Law in order to achieve regulatory harmonization. The research method employed is normative legal research with a qualitative analytical approach through a literature review. The approaches applied include the statutory approach and the conceptual approach. The primary legal sources analyzed are based on the text of the National Criminal Code and the Corruption Eradication Act, while secondary legal sources were obtained from relevant legal literature and scholarly journals. The results of the study show that the enactment of the National Criminal Code has given rise to a new paradigm of criminal punishment, shifting from a retributive-punitive (retribution) approach toward an integrative-utilitarian one that emphasizes proportional justice and restoration. Viewed through the lens of the legal relationship between the principles of lex posterior derogat legi priori and lex specialis derogat legi generali, this regulatory dualism does not result in a conflict of norms (legal antinomy), but rather a harmonious interplay of complementary regulations. The National Criminal Code serves to unify substantive criminal law through the restructuring of prison sentences, reform of the fine classification system, expansion of the concept of asset forfeiture, and the repositioning of the death penalty with a probationary period. Meanwhile, the Anti-Corruption Law remains in effect as an instrument of special procedural law (formal criminal law). The reduction of specific minimum penalties in the National Criminal Code is viewed as a step toward legal rationalization aimed at minimizing disparities in judicial rulings and optimizing the recovery of state assets in a humane manner.